2020
DOI: 10.1038/s41598-020-58909-4
|View full text |Cite|
|
Sign up to set email alerts
|

TNF-α and INF-γ primed canine stem cell-derived extracellular vesicles alleviate experimental murine colitis

Abstract: The inflammatory bowel diseases (IBD) are characterized by relapsing inflammation and immune activation diseases of the gastrointestinal tract. Extracellular vesicles, which elicit similar biological activity to the stem cell themselves, have been used experimentally to treat dextran sulfate sodium (DSS)-induced colitis in murine models though immunosuppressive potential. In this study, we investigated whether the Extracellular vesicles (EVs) obtained by stimulating inflammatory cytokine on canine adipose mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 74 publications
2
61
0
Order By: Relevance
“…Previous studies have shown that Treg and/or macrophages play an important role in IBD pathogenesis by regulating the function of neutrophils, dendritic cells, and other inflammatory cells [ 51 , 52 ]. In line with previous reports [ 19 , 20 , 53 ], our data indicated that MSC EVs could modulate macrophage polarization from M1-type to M2-type in the colons of DSS-colitic mice based on significantly enhanced Arg-1 and CD206 expression in colon macrophages. Furthermore, significantly up-regulated Tregs in TSG-EV treated colitic mice possibly played an important role in preventing intestinal inflammation by inhibiting the activity of Th1 and Th17 [ 36 , 54 , 55 ] or through interaction with macrophages [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies have shown that Treg and/or macrophages play an important role in IBD pathogenesis by regulating the function of neutrophils, dendritic cells, and other inflammatory cells [ 51 , 52 ]. In line with previous reports [ 19 , 20 , 53 ], our data indicated that MSC EVs could modulate macrophage polarization from M1-type to M2-type in the colons of DSS-colitic mice based on significantly enhanced Arg-1 and CD206 expression in colon macrophages. Furthermore, significantly up-regulated Tregs in TSG-EV treated colitic mice possibly played an important role in preventing intestinal inflammation by inhibiting the activity of Th1 and Th17 [ 36 , 54 , 55 ] or through interaction with macrophages [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that MSC EVs can mediate immunomodulatory effects through induction of regulatory T cells (Tregs) and M2-type macrophage polarization [ 20 , 33 ]. Thus, we investigated the effect of TSG-EV on specific T cell subsets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, IBD is still an incurable disease, and more and more dangerous factors that may cause adverse effects on IBD patients have been found. Along with the development of new technology and increased presence of materials, a large number of scientific experiments have been conducted to improve the conditions of IBD patients (Corbo et al, 2017;An et al, 2020). Cure and prevention are two important aspects of the process of disease treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other Articles included in the Collection have explored the use of EVs in therapeutics. For the treatment of immune-related diseases, the application of an inflammatory stimulus is shown to improve the anti-inflammatory and/or immunosuppressive potential of EVs secreted by adipose mesenchymal stem cells 5 . Cytoprotection of stressed cardiomyocytes through the use of EVs derived from mesenchymal stromal cells 6 , and the prevention of glucocorticoid-induced osteoporosis -through the suppression of osteoblasts' ferroptic pathway -by EVs extracted from bone marrow-derived endothelial progenitor 7 , were also demonstrated.…”
mentioning
confidence: 99%